The impact of China’s free trade zone policies on the development of new-quality productivity: A study on the mediating role of foreign investment - Jie, Chen Wen; Jing, Liu Jing; Saukani, Mohd Nasir Bin Mohd; Salleh, Norlida Hanim Mohd (Asian Development Policy Review, 2025)
As the core measure for China to promote institutional opening, the free trade zone (FTZ) policy plays an important role in driving economic growth and fostering new quality productivity (NEWP). This study uses panel data from 285 Chinese cities from 2012 to 2022 and employs a Difference-in-Differences (DID) model to empirically examine the impact of FTZ policies on NEWP. The study found that the FTZ policy has a significant impact on the improvement of NEWP. The empirical results show that FTZ policies significantly promote NEWP, with stronger effects observed in coastal regions, indicating regional heterogeneity. Foreign direct investment plays a key mediating role. After a series of robustness tests, such as the parallel trend test and robustness check, the conclusion still holds. The FTZ policy is an effective way to promote the development of China’s NEWP by improving the investment environment to attract foreign investment. The FTZ government strengthens the coordinated cooperation between domestic and foreign capital and builds a modern industrial system through the attraction of foreign investment by institutional opening. This study provides an important theoretical and empirical basis for improving the implementation effect of FTZ policies, promoting the development of NEWP, and fostering high-quality economic growth.